Mortal terror, volume 1 ebook - Golden, Christopher (Mortal Terror, 2024)
A vampire-flipped Dracula graphic novel in which mortality means life…and life means death.Vampires Jonathan Harker, Lucy Westenra, and Mina Murray live in underground London, trying to keep the undead city safe from the rumored mortals above who seek to give them life, only to kill them. But when the authorities refuse to believe mortals, let alone the mysterious Count Dracula, are anything more than myth, they are on their own to keep their city eternally dead.New York Times best-selling writers Christopher Golden and Tim Lebbon team up with award-winning horror and fantasy artist Peter Bergting in this graphic novel with a revamped twist on Dracula!